Effect of pomegranate and aloe vera extract on streptococcus mutans: An in vitro study - Priya Subramaniam; Shilpy Dwivedi; Eswara Uma; K L Girish Babu (Wolters Kluwer Medknow Publications, 2012)
Introduction: The aim of the present in vitro study was to evaluate and compare the antibacterial effect of pomegranate and aloe vera extracts on Streptococcus mutans. Materials and Methods: Hydroalcoholic extracts of pulp from both Punica granatum (pomegranate) and Aloe barbadensis miller (aloe vera) were prepared to concentrations of 5, 25, 50 and 100%. Pure sorbitol powder dissolved in distilled water was taken as the negative control. Streptococcus mutans (S mutans) was isolated from saliva by inoculation on to Mitus Salivarius Bacitracin (MSB) agar, which was then streaked onto agar plates containing Brain Heart Infusion. In each petridish, wells were prepared and using a sterile micropipette, 125μl of the specific concentration of the extract (pomegranate/ aloe vera/ sorbitol) was deposited in each well. This was done in triplicate for each concentration of the extracts. The effect of different concentrations of the extracts on S mutans was observed and the data was subjected to statistical analysis. Results: Pomegranate extract showed significantly higher inhibitory effect on S mutans at all concentrations (P≤0.05). On comparison of all three extracts at different concentrations, a significant difference (P≤0.05) was observed only at 50 and 100% concentrations. The inhibitory effect of pomegranate extract was significantly different when compared to aloe vera and sorbitol extracts. (P≤0.01). Discussion: Pomegranate extract has a significant antibacterial effect on S mutans at all concentrations.